The role of publics and deliberation at the environmental science-policy interface – summary paper - Wright-Arora, G; James, M; Troiano, M; Sidwell, N; Boyle, J; Barbrook-Johnson, P; Hirons, M (Agile Initiative, Oxford Martin School, 2024)
This document is a summary of a discussion paper that explores the relationship between environmental knowledge, policy and the public. It provides a set of provocative discussion questions to help funders, policy makers, practitioners, and researchers engage with these topics. The report was launched in June 2024, and the full discussion paper, as well as a recording of the launch webinar, can be found on the Agile website.